Land management on small islands based on settlement distribution patterns: studies on Sulabesi Island, Indonesia - Lisa Meidiyanti Lautetu; Hayati Sari Hasibuan; Rudy Parluhutan Tambunan (Brawijaya University, 2022)
With limited land availability, the land use and management on the small island must be sustainable. Sulabesi Island, with an area of <2000 km2, makes it one of the small islands in North Maluku and a remote island. This condition makes Sulabesi vulnerable to land loss and faced with adverse threats both environmentally and socio-economically if the allocation of residential places does not manage appropriately. The study aimed to identify the distribution of coastal settlement land with the characteristics of the island landscape, including analyzing its suitability to coastal boundaries and recommending directions for the development of coastal settlements on Sulabesi island. The method of this study used the geographic information system (GIS) to provide a spatial picture with overlaying and buffering techniques. The data analysis used topography, slope, distribution of settlements, and coastlines with collected data sources from government agencies and remote sensing, including field observations. The analysis results showed that the settlements scattered Sulabesi island randomly and separately with linear patterns, clustering, and combinations. The distribution in the island landscape was with a dominant height at 0-200 m and a slope of 0-30% or is a flat-steep plain. Besides that also shows a mismatch of utilization between the residence and the coastal border area, so land use for future settlements can do on the more proportional ground, especially outside the coastal buffer area. The results of this study's analysis can be used for further direction in regional planning and land management on small islands.